A method for preparing a waterborne epoxy resin-based super-hydrophobic composite coating
By introducing polydopamine-modified molybdenum disulfide and hydrophobically modified silica into the aqueous epoxy resin coating, the superhydrophobic composite coating is solved, and the problem of the unsatisfactory anti-corrosion effect of the aqueous epoxy resin coating is achieved, and a multiple excellent performance of the coating and an environmentally friendly and pollution-free preparation method is achieved.
Patent Information
- Application Number
- CN202310914972.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-07-25
AI Technical Summary
The existing water-based epoxy resin coatings have poor corrosion resistance to metals and are difficult to protect metals for a long time.
Polydopamine-modified molybdenum disulfide (MoS2@PDA) was prepared by solution blending method. The hydrophobic modified silica was combined with the semi-cured MoS2@PDA modified aqueous epoxy resin by a two-step spraying method to form an aqueous epoxy resin-based superhydrophobic composite coating.
The coating is achieved with excellent mechanical durability, self-cleaning, chemical stability and long-term corrosion resistance, avoiding the use of toxic and harmful organic solvents, while effectively protecting metals.
Smart Images

Figure CN116921183B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of super hydrophobic coatings, and more particularly to a method for preparing a waterborne epoxy resin-based super hydrophobic composite coating. Background Art
[0002] At present, in order to prevent metal from corrosion, a protective film is often formed on the metal surface to isolate the invasion of corrosive media. Since hydrophobic coatings have better isolation effect on corrosive ions than hydrophilic coatings, organic solvent-based epoxy resins are often selected when coating epoxy resin bonding layers on metal surfaces, which will cause huge environmental pollution and energy consumption. Therefore, using water as a solvent to replace organic solvents with serious VOCs emissions to prepare environmentally friendly epoxy resin coatings is a future development trend.
[0003] Since the surface of waterborne epoxy resin coating is hydrophilic, corrosive ions can easily penetrate into the surface of metal substrate, making it difficult to achieve long-term anti-corrosion effect. Therefore, it is necessary to introduce super-hydrophobic coating into waterborne epoxy resin coating to improve the anti-corrosion effect of the coating. Summary of the invention
[0004] To this end, the technical problem to be solved by the present invention is to provide a method for preparing a water-based epoxy resin-based super-hydrophobic composite coating to solve the problem that the existing water-based epoxy resin coating has an unsatisfactory anti-corrosion effect on metals.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a waterborne epoxy resin-based super-hydrophobic composite coating comprises the following steps:
[0007] Step (1), adding nano-molybdenum disulfide and tris(hydroxymethyl)aminomethane into ultrapure water and dispersing them evenly to obtain a molybdenum disulfide dispersion;
[0008] Step (2), after ultrasonic treatment of the molybdenum disulfide dispersion, dopamine hydrochloride is added and stirred at room temperature for reaction;
[0009] Step (3), after the reaction is completed, the reaction system is centrifuged, the lower precipitate obtained by centrifugation is washed with anhydrous ethanol, and then dried to obtain MoS2@PDA material;
[0010] Step (4), adding nano-silicon dioxide to the ethanol solution and mixing, and adding octadecyltrimethoxysilane to carry out a hydrolysis reaction under magnetic stirring, and obtaining a mixed dispersion after the reaction is completed;
[0011] Step (5), adding the MoS2@PDA material to the water-based epoxy resin emulsion for uniform ultrasonic dispersion, then adding the curing agent and continuing to stir and mix evenly, then spraying it onto the surface of the substrate with a spray gun, and placing it at room temperature for semi-curing to obtain a semi-cured epoxy resin primer;
[0012] Step (6), spraying the mixed dispersion onto the surface of the semi-cured epoxy resin primer with a spray gun, and leaving it at room temperature for curing to obtain a water-based epoxy resin-based super-hydrophobic composite coating.
[0013] In the preparation method of the above-mentioned water-based epoxy resin-based super-hydrophobic composite coating, in step (1), the particle size of nano-molybdenum disulfide is 100-200nm; the mass fraction of molybdenum disulfide in the molybdenum disulfide dispersion is 0.5-1.0wt%, and the mass fraction of tris(hydroxymethyl)aminomethane is 0.03-0.05wt%.
[0014] In the preparation method of the above-mentioned water-based epoxy resin-based super-hydrophobic composite coating, in step (2), the ultrasonic treatment time is 30 to 50 minutes; the mass ratio of dopamine hydrochloride to molybdenum disulfide is 1:(10 to 15); and the stirring time at room temperature is 6 to 8 hours.
[0015] In the preparation method of the above-mentioned water-based epoxy resin-based super-hydrophobic composite coating, in step (3), washing is performed with anhydrous ethanol for 3 to 5 times, the drying temperature is 55 to 65° C., and the drying time is 8 to 12 hours.
[0016] The preparation method of the above-mentioned water-based epoxy resin-based super-hydrophobic composite coating, in step (5), the water-based epoxy resin emulsion is obtained by adding ultrapure water to the water-based epoxy resin and mixing evenly, the mass ratio of the water-based epoxy resin to the ultrapure water is 1: (0.8-1.0); the mass ratio of the MoS2@PDA material to the water-based epoxy resin is 1: (100-120); the ultrasonic dispersion time is 2-3h; the mass ratio of the curing agent to the water-based epoxy resin is 1: 2; the stirring time after adding the curing agent is continued for 20-30min; the semi-curing time is 2-3h.
[0017] The preparation method of the above-mentioned water-based epoxy resin-based super-hydrophobic composite coating, the water-based epoxy resin is A glue in the water-based epoxy resin AB glue produced by Hangzhou Wuhuigang Adhesive Co., Ltd., and the curing agent is B glue in the water-based epoxy resin AB glue produced by Hangzhou Wuhuigang Adhesive Co., Ltd.; when spraying, a K3 spray gun is used, the distance between the spray gun nozzle and the surface of the substrate is 10 cm, and the spraying is 1 min.
[0018] The preparation method of the above-mentioned water-based epoxy resin-based super-hydrophobic composite coating, in step (4), the particle size of nano-silicon dioxide is 50-100nm; the volume fraction of the ethanol solution is 70-80%; the mass ratio of nano-silicon dioxide to the ethanol solution is 1:(8-10); the volume ratio of octadecyltrimethoxysilane to the ethanol solution is 1:(10-12); and the hydrolysis reaction time is 6-8h.
[0019] In the preparation method of the above-mentioned water-based epoxy resin-based super-hydrophobic composite coating, in step (6), during spraying, a K3 spray gun is used, the distance between the spray gun nozzle and the surface of the substrate is 10 cm, the spraying is 1 minute, and the curing time is 6 to 8 hours.
[0020] In the method for preparing the above-mentioned water-based epoxy resin-based super-hydrophobic composite coating, in step (6), after spraying, the molar ratio of the molybdenum element to the silicon element on the water-based epoxy resin-based super-hydrophobic composite coating is 1:180-200.
[0021] The preparation method of the above-mentioned water-based epoxy resin-based super-hydrophobic composite coating, in step (1), the particle size of nano-molybdenum disulfide is 100-200nm; the mass fraction of molybdenum disulfide in the molybdenum disulfide dispersion is 0.5wt% (molybdenum disulfide is prone to agglomeration when the concentration is too high, and cannot achieve good anti-corrosion performance when the concentration is too low), and the mass fraction of tris(hydroxymethyl)aminomethane is 0.04wt%;
[0022] In step (2), the ultrasonic treatment time is 30 min; the mass ratio of dopamine hydrochloride to molybdenum disulfide is 1:12.5; the stirring time at room temperature is 6 h; stirring at room temperature is to fully modify the molybdenum disulfide, if the stirring time is too short, the modification is incomplete, and if the stirring time is too long, the surface modified substance will partially detach from the surface of the molybdenum disulfide;
[0023] In step (3), the coating is washed with anhydrous ethanol for three times, the drying temperature is 60° C., and the drying time is 12 h. Too high a drying temperature will accelerate the curing and cross-linking, affect the compactness of the coating, and reduce the anti-corrosion performance.
[0024] In step (4), the particle size of nano-silicon dioxide is 50-100 nm; the volume fraction of the ethanol solution is 80%; the mass ratio of nano-silicon dioxide to the ethanol solution is 1:8.32; the volume ratio of octadecyltrimethoxysilane to the ethanol solution is 1:10; and the hydrolysis reaction time is 6 hours;
[0025] In step (5), the water-based epoxy resin emulsion is obtained by adding ultrapure water to the water-based epoxy resin and mixing uniformly, the mass ratio of the water-based epoxy resin to the ultrapure water is 1:1; the mass ratio of the MoS2@PDA material to the water-based epoxy resin is 1:100; the ultrasonic dispersion time is 3 hours; the mass ratio of the curing agent to the water-based epoxy resin is 1:2; the stirring time after adding the curing agent is continued for 30 minutes; the semi-curing time is 2 hours;
[0026] The water-based epoxy resin is A glue in the water-based epoxy resin AB glue produced by Hangzhou Wuhuigang Adhesive Co., Ltd., and the curing agent is B glue in the water-based epoxy resin AB glue produced by Hangzhou Wuhuigang Adhesive Co., Ltd.; when spraying, a K3 spray gun is used, the distance between the spray gun nozzle and the surface of the substrate is 10 cm, and the spraying takes 1 minute;
[0027] In step (6), during spraying, a K3 spray gun is used, the distance between the spray gun nozzle and the surface of the substrate is 10 cm, the spraying is 1 min, and the curing time is 6 h; after spraying, the amount of molybdenum element to silicon element on the water-based epoxy resin-based super-hydrophobic composite coating is 1:200.
[0028] The technical solution of the present invention achieves the following beneficial technical effects:
[0029] The present invention adopts solution blending method to prepare polydopamine modified molybdenum disulfide, and hydrophobically modified silicon dioxide is combined with MoS2@PDA modified waterborne epoxy resin in a semi-cured state by a two-step spraying method to obtain a synergistic waterborne epoxy resin-based super-hydrophobic coating. The coating has excellent mechanical durability, self-cleaning property, chemical stability and long-term corrosion resistance. The waterborne epoxy resin-based super-hydrophobic coating prepared by the preparation method of the present invention can avoid using toxic and harmful organic solvents in the preparation of metal anti-corrosion coatings, and can achieve effective protection of metal corrosion for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the process of PDA modification of MoS2 in an embodiment of the present invention;
[0031] Figure 2 Schematic diagram of the preparation of a waterborne epoxy resin-based super-hydrophobic composite coating in an embodiment of the present invention;
[0032] Figure 3a SEM image of MoS2 in the embodiment of the present invention (500nm);
[0033] Figure 3b SEM image of MoS2@PDA in the embodiment of the present invention (500nm);
[0034] Figure 3c TEM image of MoS2 in the embodiment of the present invention (200nm);
[0035] Figure 3d TEM image of MoS2@PDA in the embodiment of the present invention (200nm);
[0036] Figure 4a SEM image of MoS2@PDA in the embodiment of the present invention (200nm);
[0037] Figure 4b EDS image of MoS2@PDA in the embodiment of the present invention (200nm, S element);
[0038] Figure 4c EDS image of MoS2@PDA in the embodiment of the present invention (200nm, Mo element);
[0039] Figure 4d EDS image of MoS2@PDA in the embodiment of the present invention (200nm, N element);
[0040] Figure 4e EDS image of MoS2@PDA in the embodiment of the present invention (200nm, C element);
[0041] Figure 5 XRD patterns of MoS2 and MoS2@PDA in the embodiments of the present invention;
[0042] Figure 6 FT-IR images of MoS2 and MoS2@PDA in the embodiments of the present invention;
[0043] Figure 7 Raman graphs of MoS2 and MoS2@PDA in the embodiments of the present invention;
[0044] Figure 8a Physical image and CA image of EP1 coating in the embodiment of the present invention;
[0045] Figure 8b SEM image of EP1 coating in the embodiment of the present invention (5 μm);
[0046] Figure 8c SEM image of EP1 coating in the embodiment of the present invention (500nm);
[0047] Figure 8d Physical image and CA image of SC-EP1 coating in the embodiment of the present invention;
[0048] Figure 8e SEM image of SC-EP1 coating in the embodiment of the present invention (5 μm);
[0049] Figure 8f SEM image of SC-EP1 coating in the embodiment of the present invention (500nm);
[0050] Figure 9a Another SEM image of the SC-EP1 coating in the embodiment of the present invention (500 nm);
[0051] Figure 9b SC-EP1 coating in the embodiment of the present invention (500nm, C element);
[0052] Fig.9c SC-EP1 coating in the embodiment of the present invention (500nm, O element);
[0053] Figure 9d SC-EP1 coating in the embodiment of the present invention (500nm, Si element);
[0054] Fig.10 FT-IR image of SC-EP1 coating in the embodiment of the present invention;
[0055] Fig.11a XPS full spectrum of SC-EP1 coating in the embodiment of the present invention;
[0056] Fig.11b C1s peak spectrum of SC-EP1 coating in the embodiment of the present invention;
[0057] Fig.11c Si2p peak spectrum of SC-EP1 coating in the embodiment of the present invention;
[0058] Fig.11d O1s peak spectrum of SC-EP1 coating in the embodiment of the present invention;
[0059] Figures 12a to 12c Schematic diagram of the self-cleaning performance of the EP1 coating in an embodiment of the present invention;
[0060] Figure 12d to Figure 12f Schematic diagram of the self-cleaning performance of the SC-EP1 coating in an embodiment of the present invention;
[0061] Figures 13a to 13c Schematic diagram of the antifouling performance of the SC-EP1 coating in an embodiment of the present invention;
[0062] Fig.14a SC-EP1 coated blade scratching and tape peeling test diagram in the embodiment of the present invention;
[0063] Fig.14b A graph showing the variation trend of the number of times the SC-EP1 coating is peeled off and the hydrophobicity in the embodiment of the present invention;
[0064] Fig.14c SEM image (1 mm) of the SC-EP1 coated tape after 90 peelings in the embodiment of the present invention;
[0065] Fig.14d SEM image (5 μm) of the SC-EP1 coated tape after 90 peelings in the embodiment of the present invention;
[0066] Fig.15a Gravel scour test diagram in the embodiment of the present invention;
[0067] Fig.15b A graph showing the variation trend of the impact times and the hydrophobicity of the SC-EP1 coating in the embodiment of the present invention;
[0068] Fig.16a The initial state of water droplets on the surface of EP1 coating and SC-EP1 coating in the embodiment of the present invention;
[0069] Fig.16b In the embodiment of the present invention, water droplets on the surface of the EP1 coating and the SC-EP1 coating begin to freeze;
[0070] Fig.16c In the embodiment of the present invention, the water droplets on the surface of the EP1 coating have completed freezing / the water droplets on the surface of the SC-EP1 coating are in the freezing state;
[0071] Fig.16d In the embodiment of the present invention, the water droplets on the surface of the EP1 coating have completed freezing / the water droplets on the surface of the SC-EP1 coating are in the freezing state;
[0072] Fig.16e In the embodiment of the present invention, water droplets on the surface of the EP1 coating and the SC-EP1 coating complete the freezing state;
[0073] Fig.17a Polarization curves of the coating samples in the embodiment of the present invention after being immersed in 3.5wt% NaCl solution for 168h;
[0074] Fig.17b Polarization curves of the coating samples in the embodiment of the present invention after being immersed in 3.5wt% NaCl solution for 500h;
[0075] Figure 18a1 to Figure 18a3 Electrochemical impedance spectra of each coating sample after being immersed in 3.5wt% NaCl solution for 24h in the embodiment of the present invention;
[0076] Figure 18b1 to Figure 18b3 Electrochemical impedance spectra of each coating sample after being immersed in 3.5wt% NaCl solution for 168h in the embodiment of the present invention;
[0077] Figure 18c1 to Figure 18c3 Electrochemical impedance spectra of each coating sample after being immersed in 3.5wt% NaCl solution for 500h in the embodiment of the present invention;
[0078] Fig.19Equivalent circuit diagram for fitting EIS data in an embodiment of the present invention;
[0079] Fig.20a The surface morphology of the EP coating after 500h salt spray corrosion treatment in the embodiment of the present invention;
[0080] Fig.20b The surface morphology of the EP1 coating after 500h salt spray corrosion treatment in the embodiment of the present invention;
[0081] Fig.20c Surface morphology of the SC-EP1 coating after 500h salt spray corrosion treatment in the embodiment of the present invention. DETAILED DESCRIPTION
[0082] 1. Preparation of waterborne epoxy resin-based super-hydrophobic composite coating
[0083] 1.1 Preparation process of PDA-modified MoS2
[0084] (1) Experimental process of PDA modification of molybdenum disulfide
[0085] Weigh 1g of nano-MoS2, 0.08g of tris(hydroxymethyl)aminomethane (Tris), and 0.08g of dopamine hydrochloride (DA). Add the first two powders into 50mL of ultrapure water (UP) solution (pH=8.5), ultrasonically treat the mixture solution for 30 minutes, then add 0.08g of DA, and stir the mixture at room temperature for 6h. In this alkaline environment, dopamine hydrochloride can undergo self-polymerization to form polydopamine (PDA) on the surface of MoS2, which is due to the reaction between the quinone group of oxidized dopamine and its primary amino group. Transfer the solutions in the two beakers to a centrifuge tube for centrifugal separation, wash with anhydrous ethanol three times, and dry at 60°C for 12h to obtain powder samples, which are named MoS2@PDA. The reaction mechanism is as follows Figure 1 shown.
[0086] 1.2 Preparation of waterborne epoxy resin-based super-hydrophobic composite coating
[0087] The preparation process of waterborne epoxy resin-based super-hydrophobic composite coating is shown in Figure 2 , specifically including the following steps:
[0088] (1) Preparation process of MoS2@PDA modified waterborne epoxy resin coating
[0089] Weigh 0.1g MoS2@PDA powder and 10g epoxy resin component A emulsion (the A glue in the water-based epoxy resin AB glue produced by Hangzhou Wuhuigang Adhesive Co., Ltd.), put the two into a 25ml beaker, and then add 10ml ultrapure water (UP), and ultrasonically disperse it for 3h, then add 5g of component B curing agent (component B curing agent is the B glue in the water-based epoxy resin AB glue produced by Hangzhou Wuhuigang Adhesive Co., Ltd.) and stir for another 30min. After the solution is completely mixed, pour it into a K3 spray gun, keep the spray gun nozzle 10cm away from the steel plate, spray for 1min, and leave it at room temperature for 2h until it is semi-cured. It is named EP1.
[0090] (2) Preparation process of waterborne epoxy resin-based super-hydrophobic composite coating
[0091] 5 g of nano-SiO2 was weighed separately, added to a 100 mL beaker, 40 mL of anhydrous ethanol and 10 mL of ultrapure water (UP) were added, and 5 mL of octadecyltrimethoxysilane (OTS) was added to the solution and mixed, and magnetic stirring was performed for 6 h. After OTS was completely hydrolyzed, the mixed solution was poured into a K3 spray gun and sprayed on the surface of the semi-cured EP1 primer. The spraying amount was such that the molar ratio of the molybdenum element to the silicon element on the water-based epoxy resin-based super-hydrophobic composite coating was 1:200; After spraying, the final water-based epoxy resin-based super-hydrophobic composite coating was obtained by curing at room temperature for 6 h, and the prepared coating was named SC-EP1.
[0092] 2. Micromorphology and chemical composition analysis of MoS2@PDA
[0093] Figure 3a , Figure 3b The SEM images of MoS2 before and after modification. Figure 3c , Figure 3d TEM images of MoS2 before and after modification. Figure 3a , Figure 3b By comparison, it can be seen that Figure 3a MoS2 has a distinct lamellar stacking structure, the nanosheets are very thin, and the surface and edges are relatively smooth. Figure 3b It can be seen that MoS2@PDA still has a lamellar structure, but its surface becomes rough, with small nanoparticles attached, and the thickness of the lamellar layer and the edge increases. This is because DA undergoes oxidative self-polymerization on the surface of molybdenum disulfide, and the formed PDA nanospheres are wrapped on the surface of MoS2 nanosheets. Figure 3c , Figure 3d By comparison, it can be seen that in both figures, the diffraction rings of the MoS2 electron diffraction pattern are relatively obvious and have clear hexagonal diffraction points, showing a crystalline structure. Figure 3d It can be seen that MoS2@PDA has an obvious layered structure, the surface becomes rough and the thickness becomes thicker.
[0094] Figure 4a The scanning electron microscope image of MoS2@PDA is shown. From the SEM image, we can see that MoS2@PDA has a lamellar structure with a size between 200-300nm. Figure 4b , Figure 4c , Figure 4d , Figure 4e The EDS image of the characteristic elements of MoS2@PDA is displayed. S and Mo elements are its inherent elements. The presence of N and C elements indicates that PDA is successfully modified. It can be seen that the distribution range of N and C elements is larger, and the MoS2 nanosheets are successfully wrapped, indicating that PDA is successfully modified on the MoS2 surface, which also proves the successful preparation of MoS2@PDA.
[0095] Figure 5 The XRD patterns of materials MoS2 and MoS2@PDA are shown in Figure 2. By comparing the XRD patterns, we can find that the crystal structure of the modified materials can be characterized by XRD. Figure 5 It can be seen that the two materials have the same crystal diffraction peaks at 2θ=14.4°, 32.9°, 39.5°, 49.7° and 58.0°, which are the characteristic peaks of the (002), (100), (103), (105) and (110) crystal planes of MoS2, respectively, and are typical 2H phase structures. This indicates that the original crystal structure of MoS2 has not been changed after modification. In comparison, the characteristic peak intensities of MoS2@PDA at (002), (100) and (103) are weakened to a certain extent. This is because PDA is coated on the surface of MoS2, resulting in a decrease in the intensity of the characteristic diffraction peaks on multiple crystal planes, further proving that PDA has successfully modified MoS2.
[0096] Fourier transform infrared spectroscopy is used to characterize the chemical properties of MoS2 before and after modification, such as Figure 6 FT-IR spectra of MoS2, PDA, and MoS2@PDA. MoS2 and MoS2@PDA have a wavelength of 590 cm -1 The two molecules have an excited state energy level structure consisting of two resonance centers, and this structure becomes more obvious as the reaction is more complete. -1 The band may be related to the stretching vibration of the -OH group on the MoS2 surface. A comparative study was conducted on compounds from two different sources. For the PDA spectrum, the band at 3246 cm -1 and 3352cm -1The surrounding absorption bands show characteristics related to -NH stretching vibration and catechol -OH stretching vibration. These results show that different positions on the benzene ring affect the electron movement in the molecule, resulting in changes in its structure. -1 and 1513cm -1 The band is related to the vibration of benzene skeleton, 1262cm -1 The absorption peaks observed near the stretching vibrations of primary amine and CO are 3405 cm -1 、1622cm -1 、1513cm -1 、1262cm -1 The characteristic peaks appearing near the PDA spectrum are consistent with the characteristic peaks at the corresponding positions, which once again proves that MoS2 is successfully modified by PDA.
[0097] In order to further study the functional group structural characteristics of MoS2@PDA, Raman characterization was used, and the results are as follows Figure 7 As shown. MoS2 mainly has a peak at 385cm -1 and 409cm -1 There are characteristic peaks around, indicating that they come from E 21g Symmetry Phonon Raman Modes and A 1g Symmetric phonon Raman mode, 1342 cm in PDA Raman spectrum -1 and 1573cm -1 There are two broad characteristic peaks. This indicates that the molecule may be caused by two different phonon interactions. Compared with MoS2 and PDA, the absorption peak of MoS2@PDA shows a "comprehensive nature". In the Raman spectra of PDA and MoS2@PDA, the stretching vibration of the aromatic CN in the indole ring causes the absorption peak of 1353cm -1 , while the stretching vibration of CC in the pyrrole ring leads to the absorption peak at 1583 cm -1 These two fluorescence resonance enhancement mechanisms can also be used to explain this phenomenon. MoS2@PDA Raman spectrum 385cm -1 With 409cm -1 The two stronger absorption peaks are characteristic absorption peaks of MoS2, 1353 cm -1 With 1583cm -1 The two weaker absorption peaks are characteristic absorption peaks of PDA. The successful preparation of MoS2@PDA is strongly proved because these characteristic peaks are exactly the same in terms of peak height and peak position, which indicates the efficient synthesis and uniform distribution of PDA on the surface of MoS2.
[0098] 3. Analysis of the microstructure and chemical composition of the surface of water-based super-hydrophobic coating
[0099] Figures 8a to 8f The surface morphology and wettability of EP1 coating and SC-EP1 coating were analyzed by Figure 8a , Figure 8d By comparison, Figure 8a The surface of EP1 coating is hydrophilic, with a contact angle of 45.6°. Figure 8d The surface of the SC-EP1 coating is super-hydrophobic, and its contact angle is 159.2°. The surface morphology of the two coatings was observed by scanning electron microscopy. Figure 8b , Figure 8c and Figure 8e , Figure 8f By comparison, the surface of EP1 coating is flat and smooth, indicating that MoS2@PDA is well combined with water-based EP to form a dense three-dimensional network structure, and there are no obvious defects on the coating surface. Figure 8e , Figure 8f It can be seen from the two figures that the surface of the SC-EP1 coating is composed of uniform nanoparticles, forming a stable and continuous protrusion structure.
[0100] The composition of the SC-EP1 coating surface was analyzed and characterized by energy dispersive spectroscopy. Figure 9a This is the microscopic morphology of the SC-EP1 coating, which shows that it has an obvious nanoscale rough structure. Figure 9b , Fig.9c , Figure 9d As shown, EDS shows that the SC-EP1 coating is composed of three characteristic elements: C, O, and Si. The Si and O elements come from SiO2, and the uniform distribution of the C element indicates that octadecyltrimethoxysilane (OTS) has successfully modified SiO2, indicating that the superhydrophobicity of the coating surface is jointly determined by the nanopapillary structure and the hydrophobic functional groups in OTS.
[0101] The chemical composition of SC-EP1 coating was further analyzed by Fourier transform infrared spectroscopy (FT-IR), such as Fig.10 As shown, for SiO2, at 3454 cm -1 There is a vibration of hydroxyl (-OH) at 2923 cm-1, which is because silica is easily hydrolyzed in water to form Si-OH. For the OTS sample, the vibration of -1 and 2849cm -1 The peaks at 890 cm-1 are -CH3 and -CH2. -1 and 1180cm -1The peaks at 890 cm-1 and 890 cm-2 are Si-OC and Si-O-Si. During the modification process, the siloxy group (Si-OR) of OTS is hydrolyzed to form a silanol group (Si-OH). The generated Si-OH dehydrates with the -OH on the surface of silica to form a Si-O-Si bond. Subsequently, OTS is bonded to the surface of silica through a sufficient condensation reaction between R and Si. For the super-hydrophobic layer composed of OTS-SiO2, the peaks at 890 cm-1 and 890 cm-2 are Si-OC and Si-O-Si. -1 and 1180cm -1 There are characteristic peaks of Si-OC and Si-O-Si, indicating that the modification of SiO2 by OTS is successful.
[0102] X-ray photoelectron spectroscopy (XPS) was used to further analyze the chemical composition and bonding state of the SC-EP coating surface. Fig.11a The full spectrum of the SC-EP coating is shown in Figure 1. The strong peaks of O, C and Si are clearly visible. The high-resolution XPS spectra of C1s, Si2p and O1s are shown in Figure 1. Fig.11b , Fig.11c , Fig.11d As shown. The Cls spectrum can be decomposed into two peaks, -CC (283.60 eV) and -CO (285.42 eV), and these two bonds come from OTS. Fig.11c In the spectrum of Si2p, it can be decomposed into -Si-O-Si (102.22 eV) and C-Si (101.84 eV). Fig.11d The O1s spectrum contains -Si-O-Si and -CO bonds. Si-O-Si is due to the hydrolysis of the siloxy group (S-OR) of OTS to form active silanol, which will undergo condensation reaction with the hydroxyl group on the surface of SiO2 to form Si-O-Si bond. C-Si is an inherent bond in OTS. This analysis shows that silica has been successfully hydrophobically modified by OTS.
[0103] 4. Analysis of self-cleaning and anti-fouling performance
[0104] 4.1 Self-cleaning performance analysis
[0105] In actual service, the super-hydrophobic coating will inevitably be exposed to the outdoor environment, and the coating surface will be contaminated by some dust or tiny particles. In order to verify the self-cleaning performance of the coating, an appropriate amount of iron oxide powder is sprinkled on the coating surface, and the sample is tilted to an angle of 30° with the horizontal plane, and then deionized water is dripped on the prepared coating to wash away the pollutants on the coating surface, as follows Figures 12a to 12c As shown, the coating surface is contaminated by dark green iron oxide pigments. The coating surface is continuously flushed with deionized water. Figure 12b , Fig.12cIt was found that the coating surface has good hydrophilicity and low surface tension. When water droplets flush the coating surface, pollutants will flow and it is difficult to remove the surface pollutants. Figure 12d to Figure 12f Figure 3 is a schematic diagram of the self-cleaning behavior of the SC-EP1 superhydrophobic coating. When a water droplet hits the coating surface, it will quickly slide down due to the action of gravity, and the iron oxide pollutants on the coating will also roll down with the water droplet. This is because the surface of the SC-EP1 coating is in a superhydrophobic state. When the water droplet reaches the coating surface, a typical Cassie-Baxter model is formed. When the water droplet contacts the coating, the rough silica protrusion structure layer and the hydrophobic functional groups grafted thereon will trap the air in the surface gaps to form a thin air layer. On the one hand, these air layers can effectively prevent the penetration of water droplets. On the other hand, they can allow the water droplets to slide down quickly, thereby cleaning the pollutants on the surface. Therefore, the prepared SC-EP1 coating has excellent self-cleaning properties.
[0106] 4.2 Antifouling performance analysis
[0107] Fig.13a Fig.13c The antifouling performance test experiment of SC-EP1 coating is shown. Deionized water dyed with methylene blue, which is common in daily life, is selected as the contamination liquid, and then the super hydrophobic coating is repeatedly immersed in the contamination liquid. After multiple immersions, the coating surface is still very clean, without any contamination liquid dripping, and even not being soaked. Fig.13c This is because the special nano-protrusion structure on the surface of the SC-EP1 coating itself stores a large amount of air. When immersed in the polluted liquid, the surface of the SC-EP1 coating will form a continuous and dense air layer to block the penetration of pollutants. On the other hand, its surface has a large surface tension, which directly excludes the pollutant liquid from the surface of the super-hydrophobic coating. Through the above analysis, the water-based epoxy resin super-hydrophobic coating has excellent anti-fouling properties.
[0108] 5. Mechanical durability test
[0109] The mechanical durability of the SC-EP1 super hydrophobic coating was tested by blade scratching and tape peeling tests. Fig.14a As shown in the figure, after being cross-scratched by a blade and peeled off with a strong tape, the surface of the SC-EP1 coating was not penetrated by any water droplets. After being scratched by a blade, the sample was immersed in water and taken out, and the SC-EP1 coating was not peeled off by the strong tape. The scratched parts of the coating were relatively neat, and there was no obvious shedding or peeling phenomenon. Fig.14bThe change in the water contact angle of the SC-EP1 coating scratched by a blade after different stripping times. The results show that after 90 times of tape stripping, its water contact angle is still greater than 150° and the rolling angle is less than 10°, indicating that the superhydrophobic coating still maintains excellent water-repellent properties and high adhesion to the substrate. Fig.14c , Fig.14d This is the surface morphology of the super-hydrophobic coating after the tape is peeled off 90 times. Fig.14c This is the morphology of the coating at a small magnification. It can be seen that after 90 times of wear, there is no obvious shedding phenomenon at the scratch of the blade, and the coating is relatively complete. Fig.14d The above is a magnified coating morphology image. It can be seen that the nano-scale rough structure of the coating surface is not destroyed. This is because the epoxy resin of the bottom layer has strong adhesion, which makes the hydrophobically modified silica firmly bonded to the bottom epoxy resin. This shows that the SC-EP1 coating has good mechanical durability.
[0110] In order to further test the mechanical durability of the superhydrophobic coating, a gravel scouring test was carried out on the coating. In addition, 30 g of quartz sand was used to impact the prepared superhydrophobic sample from a height of 25 cm. The CA and SA values of the sample surface were recorded after each 5 impacts. The sample after impact was tilted to test whether the droplet could slide off quickly. Fig.15a This is a real picture of the gravel impact experiment. It can be seen that after 20 repeated scourings by quartz sand particles, the CA of the coating surface gradually decreases and the SA gradually increases, but in the end its surface is still in a superhydrophobic state. Fig.15b The above analysis shows that the SC-EP1 coating has good mechanical durability.
[0111] 6. Anti-icing performance analysis
[0112] Figures 16a to 16e The whole process of water droplet freezing on the surface of EP1 coating and SC-EP1 coating is shown. Table 1 shows the specific values of freezing time and freezing temperature of each coating. Fig.16a The left side shows the initial state of a water drop on the EP1 coating. Since the coating surface is hydrophilic, the water drop spreads over a large area on the EP1 coating surface. Fig.16a The water droplets on the surface of the SC-EP1 super-hydrophobic coating on the right appear to be stable spherical; Fig.16b This is a picture of the water droplets starting to freeze on the two coating surfaces. The time from the initial freezing to the freezing of the water droplets on the EP1 coating is 367s; Fig.16c The photo shows that the water droplets on the EP1 coating have completely frozen. It can be observed that the water droplets on the surface of the EP1 coating have completely turned into a "semicircle", indicating that the water droplets have completely frozen. At this time, the temperature is -9.5℃, while the SC-EP1 coating has not yet completely frozen, so it continues to be subjected to freezing experiments. Fig.16eAs shown in Table 1, the freezing state of the SC-EP1 super-hydrophobic coating is completed. The freezing completion time is 744s. The water droplets on the coating surface change from transparent to "turbid". Compared with the EP1 coating, the freezing time of the water droplets on the surface of the SC-EP1 super-hydrophobic coating is extended by 191s, and the freezing temperature is also reduced by 5°C, indicating that the SC-EP1 super-hydrophobic coating has better anti-icing function and can effectively delay the freezing time and reduce the freezing temperature. The reason for its anti-icing is that the surface of the SC-EP1 super-hydrophobic coating is super-hydrophobic, and the water droplets on the coating are in a very stable spherical shape, which reduces the contact area between the water droplets and the surface; while the pure EP surface is hydrophilic, and when the water droplets contact the coating surface, a larger contact area will be formed. Because the contact area between the two coatings and the water droplets is quite different, and the smaller the contact area, the slower the heat transfer will be, so the slower the freezing time and the lower the freezing temperature.
[0113] Table 1 Water drop freezing temperature and time on EP and SC-EP coating surfaces
[0114]
[0115] 7. Corrosion resistance test
[0116] In order to explore the anti-corrosion performance of waterborne epoxy resin-based superhydrophobic coatings, the corrosion resistance of EP, EP1, and SC-EP1 coating samples was evaluated using an electrochemical workstation.
[0117] 7.1 Potentiodynamic polarization curve
[0118] Fig.17a and Fig.17b Table 2 is the comparison of polarization curves of EP coating, EP1 coating and SC-EP1 super hydrophobic coating immersed in 3.5wt.% NaCl solution for 168h and 500h. Table 2 is the electrochemical data obtained from the polarization curves. After 168h of immersion experiment, the corrosion current density (icorr) of SC-EP1 super hydrophobic coating is 4.9x10 -10 A.cm -2 Compared with the EP coating and EP1 coating, its corrosion current density (icorr) is the lowest, which is 4 and 1 orders of magnitude lower, respectively. Even after immersion in 3.5wt.%NaCl solution for 500h, the corrosion current density (icorr) of SC-EP1 superhydrophobic coating is 4 orders of magnitude lower than that of EP coating, which is 5.6x10 -9 A.cm -2. In addition, the corrosion potential (Ecorr) of the SC-EP1 super-hydrophobic coating sample after immersion in NaCl solution for 168h and 500h is larger than that of the EP1 coating and EP. The smaller corrosion current density and larger corrosion potential indicate that the prepared SC-EP1 super-hydrophobic coating has excellent long-term corrosion resistance. The reason is that the surface wetting state of the EP coating is hydrophilic, and the external corrosive ions can easily penetrate into the surface of the substrate; the EP1 coating is added with lamellar MoS2@PDA; it can extend the path of the corrosive ions to the substrate in the coating, achieving a better anti-corrosion effect; and the hydrophobically modified OTS-SiO2 in the SC-EP1 coating can form a continuous and dense nano-rough structure, and the protruding nano-structure will form a dense air layer, making it difficult for the corrosive ions to reach the substrate. On the other hand, the MoS2@PDA in the bottom EP1 can also play a role in blocking the corrosive medium. Therefore, the anti-corrosion performance of SC-EP1 is the best.
[0119] Table 2 Comparison of polarization curve fitting parameters of coating samples after immersion in 3.5wt% Na Cl solution for 168h and 500h
[0120]
[0121] 7.2 Electrochemical Impedance Spectroscopy
[0122] Figure 18a1 to Figure 18c3 is the electrochemical impedance spectroscopy (EIS) of each coating sample, Figure 18a1 to Figure 18a3 As shown in the figure, after the coating was immersed in 3.5wt.% NaCl solution for 24h, the diameter of the capacitance loop of the SC-EP1 coating was significantly larger than that of the EP and EP1 coatings, which was 2 and 1 orders of magnitude larger, respectively, indicating that the SC-EP1 coating has better corrosion resistance. It is well known that a larger low-frequency impedance modulus (|Z|) indicates better corrosion resistance. Fig.18a3 As shown in Figure 2, the low-frequency impedance modulus of the SC-EP1 coating is significantly higher than that of the EP coating immersed for 24 hours. As the immersion time increases, the capacitance loop diameter and low-frequency impedance modulus of the SC-EP1 coating decrease significantly, as shown in Figure 2. Figure 18c1 to Figure 18c3 ), even after immersion for 500 h, the SC-EP1 coating still exhibits a large low-frequency impedance modulus (4.37x10 8 Ω·cm 2) and capacitance loop diameter, which is only one order of magnitude lower than other coatings. The results of the electrochemical impedance spectroscopy test are consistent with the polarization curve. The reason for this is that the surface of the SC-EP1 coating has a nano-rough structure and hydrophobic functional groups, so that the corrosive medium is well blocked by the air layer formed on the surface of the coating. In addition, the MoS2@PDA in the bottom EP1 can form a maze effect, extending the path of the corrosive medium to the substrate surface, and finally achieving a good synergistic effect. The results show that the prepared SC-EP1 coating has excellent long-term corrosion resistance.
[0123] In addition, in order to analyze the EIS measurement results in more detail, an equivalent circuit is used to fit the EIS spectrum. The equivalent circuit model is as follows: Fig.19 As shown, the coating resistance (R c ), coating capacitance (Q c ), charge transfer resistance (R ct ) and double layer capacitance (C dl ) c The higher the value, the better the barrier performance of the coating, which also means that the coating has fewer defects. Due to the lack of the protection of the superhydrophobic surface layer, the R c The value is much lower than that of SC-EP1 coating. Studies have shown that the invasion of corrosive ions will lead to an increase in the dielectric constant of the coating, which is manifested as Q c As shown in Table 3, the Q value of the EP coating is the largest, indicating that the aqueous solution is more likely to penetrate this coating during the immersion process. In contrast, the Q value of the SC-EP1 coating during the entire immersion period is c The value is the smallest, indicating that the coating has the best barrier performance. c It reflects the electrochemical corrosion rate of the metal interface. The R c The highest value indicates the lowest metal corrosion rate, which is due to the air layer on the surface of the super-hydrophobic coating hindering the transfer of charges. dl Directly related to the metal area exposed to the electrolyte, C dl The higher the value, the greater the degree of damage to the layer. dl The reason for the lower value is that the coating has better barrier properties and can inhibit further corrosion. High resistance indicates that the coating can effectively protect the substrate from corrosion, and low capacitance means a smaller corrosion area. In summary, the prepared SC-EP1 superhydrophobic coating has excellent long-term corrosion resistance.
[0124] Table 3 EIS data fitting results of each coating sample after immersion in 3.5wt% NaCl solution for 500h
[0125]
[0126] 7.3 Salt spray corrosion test
[0127] The three coating samples were subjected to a 500-h salt spray accelerated corrosion test in a salt spray accelerated corrosion test chamber, and the macroscopic morphologies of the coating surfaces were compared. Fig.20a It is a water-based epoxy resin coating. The cross scratches show the formation of reddish-brown Fe2O3, and the surface pitting corrosion distribution area is the largest, indicating that the corrosive medium and ions have seriously penetrated and eroded the coating, and the damage caused by corrosion is the most serious. Fig.20b It shows that the surface corrosion of the water-based epoxy resin coating added with molybdenum disulfide mainly occurs at the cross scratches, and small-scale blistering and bulging phenomena occur. The reason is that the lamellar molybdenum disulfide distributed in the coating prolongs the path of corrosive ions to reach the metal substrate, but its surface is hydrophilic and fails to achieve a more long-term and effective anti-corrosion effect. Fig.20c This is the macroscopic morphology of the surface of the SC-EP1 super-hydrophobic coating. The cross scratches have the smallest corrosion distribution range, with only a small amount of Fe2O3 generated, and no obvious pitting phenomenon at other locations of the coating. This shows that the nano-rough structure and hydrophobic functional groups formed by OTS-SiO2 particles can effectively block the invasion of corrosive media, and the air layer formed on the coating surface plays a good barrier role, slowing down the penetration of corrosive media and chloride ions. The above analysis shows that the SC-EP1 super-hydrophobic coating has the best corrosion resistance.
[0128] This embodiment successfully prepared a water-based epoxy resin-based super-hydrophobic composite coating using a two-step spraying method. It is environmentally friendly and pollution-free, and the preparation method is simple and suitable for mass production. The surface morphology and chemical composition of the coating were analyzed, and the mechanical durability, anti-icing performance, self-cleaning performance and corrosion resistance of the super-hydrophobic coating were tested, and the following conclusions were obtained:
[0129] (1) Polydopamine-modified molybdenum disulfide (MoS2@PDA) was successfully prepared by a solution blending method. MoS2@PDA was added to a water-based epoxy resin to prepare (EP1) using a two-step spraying method. OTS-SiO2 nanoparticles were then sprayed on the surface of the semi-cured EP1 coating. The resulting SC-EP1 coating had a water contact angle and sliding angle of 158.6±1° and 4±1°, respectively, and had stable superhydrophobic properties.
[0130] (2) The surface morphology and composition of the SC-EP1 coating were analyzed using modern analytical techniques and characterization methods, indicating that the nano-rough structure and chemical composition together give the SC-EP1 coating excellent superhydrophobic properties.
[0131] (3) The results of tape stripping test and gravel impact test show that the SC-EP1 coating does not lose its superhydrophobic properties after 90 tape strippings after being scratched by a blade; it also does not lose its superhydrophobic properties after 20 times of 20g gravel impact, indicating that the SC-EP1 coating has excellent mechanical durability.
[0132] (4) Self-cleaning and anti-fouling experiments show that the SC-EP1 coating can clean the dirt on the coating surface. The anti-icing experiment results show that the special rough structure of the SC-EP1 coating surface can prolong the freezing time and reduce the freezing temperature.
[0133] (5) The results of electrochemical tests and salt spray tests show that after 500 h of immersion in 3.5 wt.% NaCl solution, the SC-EP1 coating has the best anti-corrosion performance, with the corrosion current density decreasing by one order of magnitude, the lowest corrosion rate of 30.613 mpy, and a larger low-frequency impedance modulus |Z| of 4.37x10 8 Ω·cm 2 Compared with pure epoxy resin coating, it is only reduced by one order of magnitude. The test results obtained by electrochemical impedance spectroscopy are consistent with the polarization curve. The salt spray test also shows that the surface corrosion area and corrosion spot distribution of SC-EP1 coating are the smallest, the coating surface is the most complete, and its corrosion resistance is the best.
Claims
1. A method for preparing a waterborne epoxy resin-based super-hydrophobic composite coating, characterized in that: The steps include: Step (1), adding nano-molybdenum disulfide and tris(hydroxymethyl)aminomethane into ultrapure water and dispersing them uniformly to obtain a molybdenum disulfide dispersion; the particle size of the nano-molybdenum disulfide is 100-200 nm; the mass fraction of molybdenum disulfide in the molybdenum disulfide dispersion is 0.5-1.0 wt %, and the mass fraction of tris(hydroxymethyl)aminomethane is 0.03-0.05 wt %; Step (2), after ultrasonic treatment of the molybdenum disulfide dispersion, dopamine hydrochloride is added, and the mixture is stirred at room temperature for reaction; the ultrasonic treatment time is 30 to 50 minutes; the mass ratio of dopamine hydrochloride to molybdenum disulfide is 1:(10 to 15); the stirring time at room temperature is 6 to 8 hours; Step (3), after the reaction is completed, the reaction system is centrifuged, and the lower precipitate obtained by centrifugation is washed with anhydrous ethanol, and then dried to obtain MoS2@PDA material; Step (4), adding nano-silicon dioxide to an ethanol solution and mixing, and adding octadecyltrimethoxysilane to carry out a hydrolysis reaction under magnetic stirring, and obtaining a mixed dispersion after the reaction is completed; the particle size of the nano-silicon dioxide is 50 to 100 nm; the volume fraction of the ethanol solution is 70 to 80%; the mass ratio of the nano-silicon dioxide to the ethanol solution is 1:(8 to 10); the volume ratio of octadecyltrimethoxysilane to the ethanol solution is 1:(10 to 12); the hydrolysis reaction time is 6 to 8 hours; Step (5), adding MoS2@PDA material to water-based epoxy resin emulsion and uniformly dispersing by ultrasonic, then adding curing agent and continuing to stir and mix uniformly, spraying it onto the surface of the substrate with a spray gun, and leaving it at room temperature for semi-curing to obtain a semi-cured epoxy resin primer; the water-based epoxy resin emulsion is obtained by adding ultrapure water to the water-based epoxy resin and mixing uniformly, the mass ratio of the water-based epoxy resin to the ultrapure water is 1: (0.8-1.0); the mass ratio of MoS2@PDA material to the water-based epoxy resin is 1: (100-120); the ultrasonic dispersion time is 2-3 hours; the mass ratio of the curing agent to the water-based epoxy resin is 1:2; the stirring time after adding the curing agent is continued for 20-30 minutes; the semi-curing time is 2-3 hours; Step (6), spraying the mixed dispersion onto the surface of the semi-cured epoxy resin primer with a spray gun, and leaving it at room temperature for curing to obtain a water-based epoxy resin-based super-hydrophobic composite coating; After spraying, the amount of molybdenum element to silicon element on the waterborne epoxy resin-based super-hydrophobic composite coating is 1:180-200.
2. The preparation method of waterborne epoxy resin-based super-hydrophobic composite coating according to claim 1, characterized in that, In step (3), the product is washed with anhydrous ethanol for 3 to 5 times, the drying temperature is 55 to 65° C., and the drying time is 8 to 12 hours.
3. The preparation method of waterborne epoxy resin-based super-hydrophobic composite coating according to claim 1, characterized in that, The water-based epoxy resin is the A glue in the water-based epoxy resin AB glue produced by Hangzhou Wuhuigang Adhesive Co., Ltd., and the curing agent is the B glue in the water-based epoxy resin AB glue produced by Hangzhou Wuhuigang Adhesive Co., Ltd.; when spraying, a K3 spray gun is used, the distance between the spray gun nozzle and the surface of the substrate is 10 cm, and the spraying is 1 minute.
4. The preparation method of waterborne epoxy resin-based super-hydrophobic composite coating according to claim 1, characterized in that, In step (6), a K3 spray gun is used for spraying, the distance between the spray gun nozzle and the surface of the substrate is 10 cm, the spraying time is 1 min, and the curing time is 6 to 8 h.
5. The method for preparing a waterborne epoxy resin-based super-hydrophobic composite coating according to any one of claims 1 to 4, characterized in that: In step (1), the particle size of nano-molybdenum disulfide is 100-200 nm; the mass fraction of molybdenum disulfide in the molybdenum disulfide dispersion is 0.5wt%, and the mass fraction of tris(hydroxymethyl)aminomethane is 0.04wt%; In step (2), the ultrasonic treatment time is 30 minutes; the mass ratio of dopamine hydrochloride to molybdenum disulfide is 1:12.5; and the stirring time at room temperature is 6 hours; In step (3), washing with anhydrous ethanol three times, drying at 60°C, and drying time for 12 h; In step (4), the particle size of nano-silicon dioxide is 50-100 nm; the volume fraction of the ethanol solution is 80%; the mass ratio of nano-silicon dioxide to the ethanol solution is 1:8.32; the volume ratio of octadecyltrimethoxysilane to the ethanol solution is 1:10; and the hydrolysis reaction time is 6 hours; In step (5), the water-based epoxy resin emulsion is obtained by adding ultrapure water to the water-based epoxy resin and mixing them evenly, the mass ratio of the water-based epoxy resin to the ultrapure water is 1:1; the mass ratio of the MoS2@PDA material to the water-based epoxy resin is 1:100; the ultrasonic dispersion time is 3 hours; the mass ratio of the curing agent to the water-based epoxy resin is 1:2; the stirring time after adding the curing agent is continued for 30 minutes; the semi-curing time is 2 hours; In step (6), during spraying, a K3 spray gun is used, the distance between the spray gun nozzle and the surface of the substrate is 10 cm, the spraying is 1 minute, and the curing time is 6 hours; after spraying, the molar ratio of the molybdenum element to the silicon element on the water-based epoxy resin-based super-hydrophobic composite coating is 1:200.
Citation Information
Patent Citations
Preparation method of persistent icing-resistant superhydrophobic coating
CN106883650A
Preparation method of polydopamine modified molybdenum disulfide composite epoxy powder coating
CN113637383A